The Correlation between the Students’ Language Learning Strategies and Their English Proficiency - Yusmalinda Yusmalinda (LINGUA LITERA : journal of english linguistics and literature, 2020)
Abstract This research aimed at finding out the degree of the correlation between students’ learning strategies and their English Proficiency. It was based on the rationale that students still had problems with their English proficiency and did not know what to do to improve it. On the other hand, there are some successful language learning strategies that can be applied based on some experts to help them. To find out whether there was positive correlation between students’ language learning strategies, data were collected. To collect the data about language learning strategies, a questionnaire was used which had been tried out to know its validity and reliability. To find out the students English proficiency, TOEFL was used. To test the hypothesis, the results of questionnaire and TOFL were correlated by using Pearson Product Moment. The hypothesis was tested by comparing r computed with the Pearson table on the level of significance 0.05. The result of r computed was 0.523, and the critical value was between 0.325 and 0.304 with the degree of freedom 37 (n-2). It was found that the value of r computed was higher than the Pearson table r value. It can be concluded that there was a positive correlation between students’ language learning strategies and their English proficiency. In other words, the research hypothesis was accepted.